2015
DOI: 10.1038/mt.2015.115
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infection of Tumors Overcomes Resistance to PD-1-immunotherapy by Broadening Neoantigenome-directed T-cell Responses

Abstract: There is evidence that viral oncolysis is synergistic with immune checkpoint inhibition in cancer therapy but the underlying mechanisms are unclear. Here, we investigated whether local viral infection of malignant tumors is capable of overcoming systemic resistance to PD-1-immunotherapy by modulating the spectrum of tumor-directed CD8 T-cells. To focus on neoantigen-specific CD8 T-cell responses, we performed transcriptomic sequencing of PD-1-resistant CMT64 lung adenocarcinoma cells followed by algorithm-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
164
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(171 citation statements)
references
References 47 publications
2
164
0
1
Order By: Relevance
“…Soluble CD80 mediated intervention of PD-1/PD-L1 axis can restore the activation of both CD4 + and CD8 + T cells with IFN-γ production [34,35]. Virotherapy using oncolytic viruses has been reported to reduce the systemic resistance to PD-1 immunotherapy in an experimental model of liver cancer, thus providing the rationale for combining oncolytic viruses and immune checkpoint blockade in clinical trial [36]. Immune checkpoint receptors are recognized as important players of immune suppression in HCC [37,38].…”
Section: Inhibitory Checkpoint Receptors and “T Cell Exhaustion”mentioning
confidence: 99%
“…Soluble CD80 mediated intervention of PD-1/PD-L1 axis can restore the activation of both CD4 + and CD8 + T cells with IFN-γ production [34,35]. Virotherapy using oncolytic viruses has been reported to reduce the systemic resistance to PD-1 immunotherapy in an experimental model of liver cancer, thus providing the rationale for combining oncolytic viruses and immune checkpoint blockade in clinical trial [36]. Immune checkpoint receptors are recognized as important players of immune suppression in HCC [37,38].…”
Section: Inhibitory Checkpoint Receptors and “T Cell Exhaustion”mentioning
confidence: 99%
“…A preclinical study demonstrated oncolytic activity in response to stereotactic body radiation therapy (SBRT) in mice bearing liver tumors [35]. Another study showed immune response to oncolytic adenovirus in mice with lung metastases from a liver cancer [36]. These studies consistently showed a CD8+ T cell response by oncolytic treatment.…”
Section: Immunotherapeutic Preclinical and Translational Approaches Tmentioning
confidence: 98%
“…These studies consistently showed a CD8+ T cell response by oncolytic treatment. However, a complete antitumor response could only be elicited in combination with a PD-1 checkpoint inhibitor [35,36].…”
Section: Immunotherapeutic Preclinical and Translational Approaches Tmentioning
confidence: 99%
“…Показано, что кроме лизиса опухолевых клеток онколитические вирусы стимулируют развитие опухолеспецифичного Т-клеточного ответа, по крайней мере столь же эффективно, как и блокаторы иммунных контрольных точек [89]. С помощью введения в геном онколитического вируса раковых антигенов можно дополнительно повысить эффективность индукции противоопухолевого иммунного ответа.…”
Section: Nepomnyashchikh Ts Et Al непомнящих тс и др Medical Imunclassified